The snowy day - Keats, Ezra Jack. (Harmondsworth New York Puffin Books, 1978)
The adventures of a little boy in the city on a very snowy day.
"Caldecott Award book."
UCWS-2014-G-2111 donated by Jan Gabriel M. Castaneda
Keywords: Snow -- Fiction; African Americans -- Fiction